USING OF REMOTE SENSING TECHNIQUES TO ESTIMATE THE BIOMASS CHINGES OF SELECTED FOREST SITES IN NORTHERN IRAQ. - Basman Younis Hameed (Mesopotamia Journal of Agriculture)
The purpose of this study is to use Landsat TM data to prepare Thematic Formulas for estimating the changes occurred in upper-ground biomass of Pinus brutia forestry north Iraq represented by Acra, Atroosh and Zaweeta plantations during 1989-2001. The study adopted the formula: Y=23.5591+2.10785x10.723153+22.9213(x2/100)8.5607 to estimate the Biomass where Y is total wet weight of the study samples, x1 represents the reflectance values of the vegetation cover in band3 of TM sensor, while x2 represents the reflectance values of vegetation cover in band4 TM. The study revealed that there is a progressive in biomass in large number of samples within the plantation area that is range between (0.086028-19.021487) ton/hectare and this result represent a big range of change in biomass depending basically on the environments parameters because the studied plantations are distributed widely comprising Acra, Atroosh and Zaweeta which characterized by different topography and aspects in addition to the bad human activities that affected the progressive and growth of plantations, and this has been cleared by the descending of growth in some sites of the study area.